(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2010)
The aim of this research project is to study the detailed research on hacking, hacking tools & anti hacking tools by taking hacking examples. In it we will study the history behind hacking & the various types of hackers. Our aim is basically to study how the intruders detect the systems & intrusion scenarios. The paper describes in detail the various anti hacking tools like firewalls, encryption, antivirus, authorization etc.The paper also gives an overview about passwords & types of password attacks & also about the recent Cell Phone Hacking & IT Act 2000.